Testing otter board hydrodynamic performances in wind tunnel facilities. (1st August 2015) - Mellibovsky, Fernando; Prat, Joana; Notti, Emilio; Sala, Antonello
Abstract: The feasibility and potential advantages of wind tunnel testing of otter board designs are assessed. Traditional flume tank tests incur high operational costs and present some limitations in terms of flexibility and accuracy. Modern flume tanks, despite more flexible and accurate, are still expensive to operate or hire. Wind tunnel facilities are widespread, with a potential for low budget tests, and allow for an accurate control of velocity, angle of attack and sideslip as well as precise measurement of forces and moments in all three axes. A complete description of otter board hydrodynamics is paramount to optimising design and rigging and for the design of active control strategies that allow for stable trawling at a target speed and depth. We describe in detail the methodology of wind tunnel tests applied to general otter board designs, exemplify it with a commercial pelagic otter board and provide a comparison with existing flume tank results for the same design. Abstract : Highlights: We present and demonstrate a method to exploit wind tunnel facilities in otter board testing. We apply notions and approaches from aeronautics and flight mechanics to analyse otter board performances. Wind tunnels can provide an accurate description of the otter board hydrodynamics at a low cost. Wind tunnel output includes important performance data such as the centre of pressure or forces and moments in all three axes.